Conference Report: Moving forward together: "we are making progress". (May 2014) - van Dongen, William D; Renfurm, Luuk C
The 6th European Bioanalysis Forum Open Meeting 20–22 November 2013, Hesperia Tower Hotel, Barcelona, Spain At the 6th European Bioanalysis Forum Open Meeting, held from 20–22 November 2013 in Hesperia Tower Hotel, Barcelona, Spain, bioanalytical experts from pharmaceutical industry, academia, contract laboratories and regulatory bodies discussed current topics of interest in bioanalysis. 450 delegates from more than 170 institutes and companies participated in 75 open and stimulating presentations regarding the new US FDA Guidance for industry, technology updates, including liquid chromatography–mass spectrometry of proteins and antibody-drug conjugates, dried blood spots, sampling and extraction and regulatory aspects of, for example, flow cytometry, parallelism, and interferences in ligand-binding assays. This article aims to provide an overview of the highlights discussed at the meeting.